BAHASA SEBAGAI MEDIA EKSPRESI RASA DALAM PUISI “KEPADA ABU” KARYA NATASHA RIZKY - Salsabila, Intan; Anzani, Nurul Afni; Yunus, Syarifudin (Cahaya Ilmu Bangsa Institute, 2025)
Abstract Poetry is a form of expression that conveys a poet's feelings through distinctive diction and language style. This study analyzes how language is used as a medium for emotional expression in Natasha Rizki's poem